Pacific modulation of the North Atlantic storm track response to sudden stratospheric warming events ... - Afargan-Gerstman, Hilla; Domeisen, Daniela (ETH Zurich, 2020)
Geophysical Research Letters, 47 (2) ... : ISSN:0094-8276 ...